'Hub‐and‐spoke' pilot in Wisconsin would target all SUDs. Issue 34 (27th August 2021) - Knopf, Alison
Abstract : Vermont started the hub‐and‐spoke system originally almost 10 years ago (see ADAW, Oct. 29, 2012). It was funded by the federal government's new insurance plan and included the hubs (opioid treatment programs that provided both methadone and buprenorphine for patients who needed more comprehensive care, and patients being started on treatment or assessed for care) and spokes (buprenorphine prescribers). Since then, other states and entities have adopted their own versions of "hub‐and‐spoke, " using that terminology but not the exact model.